The evolving landscape of pediatric obesity and metabolic dysfunction-associated steatotic liver disease - Putri, Resthie R. (Frontiers in Pediatrics, 2025)
The global rise in pediatric obesity has paralleled an alarming increase in metabolic dysfunction-associated steatotic liver disease (MASLD), formerly known as non-alcoholic fatty liver disease (NAFLD). MASLD in children represents a significant public health concern due to its potential progression to advanced liver disease and its association with a myriad of cardiometabolic comorbidities. This review elucidates the risk and consequences of pediatric MASLD in the population of children with obesity. It also identifies critical research gaps and outlines future directions for the prevention, diagnosis, and treatment of pediatric MASLD.